Athlete development in Norwegian handball - Thue Bjørndal, C.; Ronglan, L. T. (Talent identification and development in sport. International perspectives, 2021)
Based on an explanatory overview of Norwegian sport structure, this chapter explains and examines the unique approach to athlete development in Norwegian handball. Norwegian handball is characterised by sustained international success and broad participation. Since the year 2000, the women's international team has won 14 medals in the European Women's Handball Championship, the IHF World Women's Handball Championship, and the Olympic Games (including 11 gold medals across all competitions). Meanwhile, the Norwegian national men's team won two silver medals at the IHF World Men's Handball Championships in 2017 and 2019. The chapter is divided into four sections. First, we provide a brief review of the applied athlete development model in Norwegian handball. Second, we highlight the challenges and opportunities for talent development in Norway's multi-centric model. Third, we discuss strategies for managing athlete development within this organisational context. Finally, we summarise the key points, reflecting on the potential value of our findings for researchers and practitioners.